A One‐pot Approach to Ethyl 1, 4, 5‐Triaryl‐1H‐pyrazole‐3‐carboxylates via an Improved Claisen Condensation‐Knorr Reaction Sequence. Issue 12 (11th December 2013) - Zhai, Jiaojiao; Gu, Chunhui; Jiang, Jianan; Zhang, Shunli; Liao, Daohua; Wang, Lei; Zhu, Dunru; Ji, Yafei
Abstract A one‐pot approach to ethyl 1, 4, 5‐triaryl‐1H‐pyrazole‐3‐carboxylates has been developed in moderate to high yields. The tert‐BuOLi‐mediated Claisen condensation of 1, 2‐diarylethanones and ethyl oxalyl chloride efficiently provided the enolized lithium salts of ethyl 2, 4‐dioxo‐3, 4‐diarylbutanoates, which in situ reacted with arylhydrazine hydrochlorides via a hydrochloric acid‐promoted Knorr reaction to produce the exquisite triarylpyrazole‐3‐carboxylates. The procedure promises a convenient access to this highly crowded framework for drug discovery.